2013
DOI: 10.1111/wre.12035
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in sprouting capacity from intact rhizome systems of three perennial weeds

Abstract: Summary The three rhizomatous perennials Elytrigia repens, Equisetum arvense and Tussilago farfara are all problematic in Scandinavian agriculture, due to their low susceptibility to soil cultivation. While repeated soil tillage is a fundamental part of the integrated control of these species, it is highly energy consuming and inefficient during periods when little sprout regrowth occurs. Substituting cultivation with mowing will reduce the environmental impact and labour costs, but its efficiency will still d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Main control methods of E. repens include herbicides and intensive tillage, although competitive crops are essential for keeping E. repens under control (Cussans, 1968(Cussans, , 1970. However, as E. repens can continue to build rhizome biomass well into the autumn (Boström et al, 2013), attempts have been made to use under-sown companion crops to extend the period of intensive competition post-harvest -with varying levels of success. Experiments have shown that under-sown companion crops can cause a significant reduction in E. repens rhizome biomass (Cussans, 1972;Bergkvist et al, 2010), but also that shoot biomass can be reduced without affecting rhizome biomass (Ringselle et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Main control methods of E. repens include herbicides and intensive tillage, although competitive crops are essential for keeping E. repens under control (Cussans, 1968(Cussans, , 1970. However, as E. repens can continue to build rhizome biomass well into the autumn (Boström et al, 2013), attempts have been made to use under-sown companion crops to extend the period of intensive competition post-harvest -with varying levels of success. Experiments have shown that under-sown companion crops can cause a significant reduction in E. repens rhizome biomass (Cussans, 1972;Bergkvist et al, 2010), but also that shoot biomass can be reduced without affecting rhizome biomass (Ringselle et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, timing is crucial, as it is likely that the resulting emergence of new shoots after cultivation is dependent on the seasonal variation in sprouting capacity. Reduced sprouting during autumn has been shown for intact rhizome systems (Boström et al ., ) as well as for isolated fragments of T. farfara (Liew, ).…”
Section: Discussionmentioning
confidence: 99%
“…As the growth in clones from southern Sweden are likely to start first in a common garden experiment (e.g. Boström et al 2013), we were unable to separate the clone effect from that of onset of growth and growth rate at time of herbicide treatment. Third, there were no genetic patterns to suggest that resistant clones would have spread in Sweden.…”
Section: No Evidence Of Selection Towards Resistance In Swedish Elymumentioning
confidence: 99%